2002
DOI: 10.1139/z02-053
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of resident and wandering prairie voles, Microtus ochrogaster

Abstract: Many studies have documented intraspecific differences in the behavior of males or females. In some species, many adults are territorial while others have larger home ranges encompassing multiple territories. Although these two types of behavior have been documented, they are not well understood in mammals. Therefore, in the mono gamous prairie vole (Microtus ochrogaster) we characterized individuals that engage in these two behavior patterns as residents and wanderers. We monitored populations enclosed in 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 24 publications
7
77
0
Order By: Relevance
“…In natural prairie vole populations, approximately one-half of males "wander" across multiple female territories attempting to mate with multiple females Solomon and Jacquot, 2002), and the biological basis of this variation continues to be studied (Fink et al, 2006;Young and Hammock, 2007;Ophir et al, 2008;Mabry et al, 2011). It was shown previously that environmental factors also contribute to mating strategy in this species as male prairie voles do not show partner preferences after long-term cohabitation unless pregnancy is established soon after pairing (Curtis, 2010).…”
Section: Fecundity and Pair Bondingmentioning
confidence: 99%
“…In natural prairie vole populations, approximately one-half of males "wander" across multiple female territories attempting to mate with multiple females Solomon and Jacquot, 2002), and the biological basis of this variation continues to be studied (Fink et al, 2006;Young and Hammock, 2007;Ophir et al, 2008;Mabry et al, 2011). It was shown previously that environmental factors also contribute to mating strategy in this species as male prairie voles do not show partner preferences after long-term cohabitation unless pregnancy is established soon after pairing (Curtis, 2010).…”
Section: Fecundity and Pair Bondingmentioning
confidence: 99%
“…Unlike neighbours, strangers (i.e., so called "wanderers"; McGuire and Getz 1998) generally do not own a territory or have a mate and hence are more likely to compete with a resident (Temeles 1994). These wanderers might be recently dispersing individuals or individuals that could be exhibiting alternative mating tactics (Solomon and Jacquot 2002). A territory holder learns to recognize or discriminate neighbours from strangers (Ydenberg et al 1988;Temeles 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Males of a few species across a broad range of taxa display pair-living and copulate with their partner rather than with novel females (Lukas and Clutton-Brock, 2013). Although some of these males occasionally come in contact with other females and engage in extra-pair copulations (Solomon and Jacquot, 2002;Cohas and Allaine, 2009;Streatfeild et al, 2011), most share a home range with one female for an extended period of time and some even participate in parental care (Reichard, 2003). Studies from a variety of species that have attempted to explain why some males forgo their mating opportunities to invest in their family have produced contradictory results (Dobson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, observations of prairie voles under natural and semi-natural settings have shown that the behavior of both males and females is dynamic and can shift from exclusive mating with a single partner to occasional mating with a novel conspecific (Solomon and Jacquot, 2002;Ophir et al, 2008;McGuire and Getz, 2010). For example, wild male prairie voles are reported to switch their mating tactics from being residents that share a home range with a single female to being wanderers that visit multiple nests (Solomon and Jacquot, 2002;Ophir et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation